2001
DOI: 10.1515/bchm.2001.382.5.853
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of ras-Transformed Breast Epithelial Cells Depends on the Proteolytic Activity of Cysteine and Aspartic Proteinases

Abstract: It has been suggested that the lysosomal proteinases cathepsin B, L and D participate in tumour invasion and metastasis. Whereas for cathepsins Β and L the role of active enzyme in invasion processes has been confirmed, cathepsin D was suggested to support tumour progression via its pro-peptide, rather than by its proteolytic activity. In this study we have compared the presence of active cathepsins B, L and D in ras-transformed human breast epithelial cells (MCF-10A neoT) with their ability to invade matrigel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…3). It is generally accepted that cathepsin L plays a role in metastasis through its extracellular activities once it has been secreted (22,26,27,30,52). Our results lead us to propose that cathepsin L also plays a role within cells and notably within the nucleus where it can change the properties of some transcriptional regulators.…”
Section: Inhibition Of Intracellular Cysteine Protease Activity Delaysupporting
confidence: 60%
“…3). It is generally accepted that cathepsin L plays a role in metastasis through its extracellular activities once it has been secreted (22,26,27,30,52). Our results lead us to propose that cathepsin L also plays a role within cells and notably within the nucleus where it can change the properties of some transcriptional regulators.…”
Section: Inhibition Of Intracellular Cysteine Protease Activity Delaysupporting
confidence: 60%
“…Transfection of cystatin C cDNA into B16 melanoma cells led to an inhibition of tumor cell invasion through an artificial matrix barrier in vitro and to a significant reduction of the number of lung metastases after the injection into the tail vein of nude mice Cox, 1997, Cox et al, 1999). The inhibitory effect of cystatin C on tumor cell invasion was also demonstrated in in vitro Matrigel invasion assays using transfected murine SCC-VII squamous carcinoma cells, ras-transformed breast epithelial cells, human fibrosarcoma, and colon carcinoma cell lines (Corticchiato et al, 1992;Coulibaly et al, 1999;Premzl et al, 2001). …”
Section: Proteolytic Systems As Therapeutic Targetmentioning
confidence: 78%
“…Recent studies have shown that cathepsins B, H and L are involved in cancer progression either by direct degradation of extracellular matrix (type I and IV collagen, laminin) or by activation of other proteases. Studies using inhibitors of cathepsins, natural inhibitors such as cystatins as well as synthetic inhibitors, demonstrated their capacity to reduce tumor cell invasion in vitro (Corticchiato et al, 1992;Coulibaly et al, 1999;Premzl et al, 2001;Sever et al, 2002;Colella et al, 2002). progression and metastasis (summarized in Brand, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CLIK 148, a specific cathepsin L inhibitor, also reduced the invasion of tumor cells through Matrigel. 30 To unambiguously establish the involvement of cathepsin L in the proteolytic cascade during glioblastoma cell invasion, we have stably transfected human glioblastoma IPTP cells with the constructs that contained the complete coding region of cathepsin L in antisense and sense orientation. Our results demonstrate that a successful transfection with cathepsin L antisense construct led to decreased cathepsin L enzymatic activity and protein content, compared with nontransfected parental cell line and control cells transfected with the vector /GFP Figure 7 Time course of caspase -3 activation after STS exposure of human glioblastoma clones.…”
Section: Discussionmentioning
confidence: 99%